Convergence and Divergence of Regional Income Distributions and Welfare - Bishop, John A.; Formby, John P.; Thistle, Paul D. (The Review of Economics and Statistics, 1994)
John A. Bishop, John P. Formby, Paul D. Thistle, Convergence and Divergence of Regional Income Distributions and Welfare, The Review of Economics and Statistics, Vol. 76, No. 2 (May, 1994), pp. 228-235